Chemical composition of essential oil from the aerial parts of Santolina rosmarinifolia L. a wild Algerian medicinal plant - SARRI Djamel (Université de M'sila, 2021)
The analysed essential oil in this study was obtained by hydrodistillation from the aerial parts of Santolina rosmarinifolia L. (Asteraceae) collected from Hodna area of Algeria. This species is a medicinal herb traditionally used in Algeria, its essential oil has been analysed by combining GC-FID and GC-MS. The analysis led to the identification of eighty-two components, representing 91.84% of the whole composition of the sample. The main components were capillene (32.79%), 1,8-cineole (15.08%) and β-myrcene (13.98%), representing more than 61% of the total oil
Keywords: Santolina rosmarinifolia L., Asteraceae, Essential oil, GC-MS Analysis, Algeria.